“Erased in Translation”: Decoding Settler Colonialism Embedded in Cultural Adaptations to Family Group Conferencing (FGC) - Hung-Peng Lin; Emiko Tajima; Karina L. Walters; Marilee Sherry (Social Sciences)
Māori wisdom revolutionized the child welfare system through the now manualized Family Group Conferencing method. The global trend of adopting and adapting this culturally grounded child welfare practice has been well documented. However, as this service model is adapted and imported to other countries, so is its legacy of settler colonialism. This qualitative case study applies Settler Colonialism Theory to unpack the settler colonialism embedded in the process of adopting an adapted Indigenist family engagement program in Taiwan. Research findings indicate that cultural adaptation reproduces settler colonialism. To implement family engagement within a paternalistic CPS system, program implementers struggled between authoritative decision making and building meaningful state–family partnerships. Although adhering to a model that ostensibly involves family decision making may ease settler anxiety among program implementers, settler colonialism remains the elephant in the room. It frequently undergirds the cultural adaptation process. Liberatory social work practice calls for unpacking settler anxiety, systems of power, and cultural imperialism embedded in program implementation.